Dampak Kebiasaan Belajar Peserta Didik dalam Meningkatkan Hasil Tes Literasi Asesmen Kompetensi Minimum (AKM) Kelas - Nurul Aulia, Shafa; Megawanti, Priarti (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Each individual has their habits that differ from one another. Each student is different, and each individual has different thinking, feeling, and acting. Different habits are a form of the uniqueness of each individual. Everyone has different habits from one another. In this case, the difference is not that something is wrong, but one of the key factors underlying the person's growth. Habits can trigger and shape the interests that someone owns. Study habits formed in each student will usually be seen later in the final results of learning, either on exams, just daily tests, or something big like a final graduation exam. This study uses observation and interview methods. This study explains whether students' study habits can affect the learning outcomes obtained by students.